War of Independence, Afro-descendants and Slavery in México - Hernández-Jaimes, Jesús (2022)
This article aims to analyses the participation and impact of people of African descent in New Spain’s independence war. It highlights the predominantly popular character of the Independence movement and concentrates on one of the regions where communities of African descent are most numerous. As a result, this social group played an important role in the the rebelling armies, to the extent that some of their members tried unsuccessfully to take control of the insurgent project. As was the case in all Spanish America, creole leadership dominated. Despite this, insurgent leaders in New Spain were early proponents of the absolute and immediate abolition of slavery. After independence, slave owners demanded compensation for enslaved people’s emancipation, which prevent this policy from being fully achieved. Fortunately, the arrival of a president of African descent and insurgency leader, allowed the formal abolition of slavery in 1829. As a result, Mexico became the first Spanish American country to extinguish this dreadful institution.